ANALISIS PERBANDINGAN KATA BANTU BILANGAN INDIVIDUAL BAHASA MANDARIN DENGAN KATA BANTU BILANGAN INDIVIDUAL BAHASA INDONESIA - Susiyati S; Lina l (Fakultas Sastra Universitas Darma Persada, 2021)
The number of Chinese noun quantifiers is very rich, and the usage is very complicated. Different nouns have different matching quantifiers. This situation makes Indonesian students prone to errors when learning quantifiers. Therefore, this article tries to compare Chinese individual noun quantifiers with Indonesian corresponding individual noun quantifiers. This article compares and analyzes one-to-one, one-to-many and many-to-one individual noun quantifiers and finds the similarities and differences between Chinese and Indonesian individual noun quantifiers.